OPTIMASI SIFAT MEKANIS TANAH LUNAK DENGAN PENAMBAHAN BAMBOO CHIPS DAN FLY ASH - Karina Jelita Putri; Dian Purnamawati Solin; Karina Meilawati Eka Putri (JITSi : Jurnal Ilmiah Teknik Sipil, 2026)
Abstract— Soft soil, which is extensively distributed along the coastal regions of Indonesia, poses a significant geotechnical challenge to infrastructure development due to its characteristically low shear strength and high settlement potential. Consequently, ground improvement measures are imperative to ensure the stability and safety of structures constructed upon such deposits. Several studies have investigated the utilization of environmentally sustainable materials as alternatives for soft soil stabilization, including the incorporation of fly ash a pozzolanic industrial by-product that enhances interparticle bonding through cementitious reactions and bamboo fibre as a discrete mechanical reinforcement element proven to improve compressive strength and bearing capacity. Premised upon these findings, the present study combines both materials in the form of bamboo chips and fly ash to exploit the synergistic interaction between physical reinforcement and chemical stabilization mechanisms. This study aims to analyze the effect of bamboo chips and fly ash addition on the mechanical properties of soft soil and to determine the optimum mixture composition. Laboratory experiments were conducted comprising compaction (Proctor), Unconfined Compressive Strength (UCS), and California Bearing Ratio (CBR) tests, with bamboo chips variations of 25%, 30%, and 35% and a constant fly ash content of 15%. The results demonstrate that the most effective variation was achieved at 25% bamboo chips and 15% fly ash, yielding an undrained cohesion (Cu) of 200.345 kN/m² and a CBR value of 14.67% at 65 blows, which produced the most substantial improvement in both strength and bearing capacity of the soft soil relative to all other investigated variations. Keywords — Soft soil, Soil stabilization, Bamboo chips, Fly ash Abstrak— Tanah lunak yang tersebar luas di wilayah pesisir Indonesia menjadi tantangan serius dalam pembangunan infrastruktur akibat kuat geser yang rendah dan potensi penurunan yang tinggi. Oleh karena itu, diperlukan upaya perbaikan tanah agar struktur yang dibangun di atasnya dapat berdiri dengan aman dan stabil. Beberapa penelitian mengkaji penggunaan material ramah lingkungan sebagai alternatif stabilisasi tanah lunak, di antaranya penambahan fly ash yang bersifat pozzolan untuk meningkatkan ikatan antar partikel tanah, serta serat bambu sebagai elemen perkuatan mekanis yang terbukti meningkatkan kuat tekan dan daya dukung tanah. Berdasarkan hal tersebut, penelitian ini mengkombinasikan keduanya dalam bentuk bamboo chips dan fly ash untuk memanfaatkan efek sinergis antara perkuatan fisik dan stabilisasi kimia. Penelitian ini bertujuan untuk menganalisis pengaruh penambahan bamboo chips dan fly ash terhadap sifat mekanis tanah lunak serta menentukan kadar campuran optimumnya. Pengujian dilakukan melalui serangkaian uji laboratorium meliputi pemadatan (Proctor), UCS, dan CBR dengan variasi bamboo chips sebesar 25%, 30%, dan 35% serta fly ash sebesar 15%. Hasil penelitian menunjukkan bahwa variasi paling efektif pada penambahan bamboo chips 25% dan fly ash 15%, dengan nilai Cu sebesar 200,345 kN/m2 dan nilai CBR sebesar 14,67% pada 65 tumbukan, yang memberikan peningkatan kekuatan dan daya dukung tanah lunak dibandingkan variasi lainnya. Kata kunci — Tanah lunak, Stabilisasi tanah, Bamboo chips, Fly ash